Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
f(g(3)) = 26
Step-by-step explanation:
f(g(3))
g(3) = 2x + 3
= 2(3) + 3
= 6 + 3
= 9
f(9) = 3x - 1
= 3(9) - 1
= 27 - 1
= 26
plug in 3 for g(x) which is 9 then plug in 9 for f(x) which is 26
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.